Pengaruh Ekspor Ikan Tongkol/Tuna Indonesia Ke Jepang Terhadap Pertumbuhan Ekonomi Di Indonesia Dengan Model Dinamis Regression - Devi Andriyani; Try Wahyu Syahputra (LPPM UNIMAL, 2021)
This study aimed to determine the effect of Tuna exports from Indonesia to Japan on the economic growth in Indonesia. This study used time series data during 2002-2015 obtained from the Central Bureau of Statistics. The data analysis method used in this study was the Vector Autoregression (VAR) approach. The results showed that the Indonesian Tuna exports to Japan had a negative and insignificant effect on economic growth. While the results based on the impulse response analysis can be said that when a shock occurs in economic growth, it takes one year so that Tuna exports can return to reach its equilibrium or equilibrium point. Based on the analysis of variance decomposition, it can be concluded that the exports of Tuna make a large contribution to economic growth.Keywords:Economic Growth, Tuna Exports from Indonesia